Notochord development in Atlantic salmon (Salmo salar L.): exploring molecular pathways and putative mechanism of segmentation - Wang, Shou (Cell and Tissue Research, 2014)
Background: A key feature of the vertebrate body plan is the repeated compartments made up of individual vertebra, blood vessels, peripheral nerves and muscle. The vertebral column comprises a series of bony vertebral bodies with arches and intervertebral discs and joints. However, the biological mechanisms that generate this segmental pattern during embryogenesis are not fully understood. Unlike amniotes, teleosts display segmented mineralization in the notochord sheath, as the initial morphogenic step in the formation of the vertebral column. It has been hypothesized that the notochord initiates its early segmentation, and thus patterns the vertebral column in teleosts. In order to determine whether the notochord is functionally segmented, this project studied all the genes expressed in the notochord prior to and during the early stages of segmentation. Studies of this type may provide further clues to the patterning of notochord segmentation in fish and possible other vertebrates. Methods A micro-dissection protocol was developed to isolate the pure cellular core of the notochord, and the rest of tissues from Atlantic salmon larvae for total RNA extraction. Two DNA-sequencing technologies, EST sequencing and RNA-seq, were employed to identify the notochord-specific transcriptome in salmon. Quantitative gene expression analysis (Q-PCR) was performed on genes of interest, and spatial gene expression in the notochord was investigated by means of in situ hybridization. Meanwhile, TEM was used for detailed characterization of the pattern of mineralization in the collagen matrix in the notochord sheath, as well as on the outside. Synchrotron radiation based X-ray diffraction was performed in order to analyze the identity of the mineralized elements in the notochord sheath. Results Mineralized ring-structures of the vertebral centra were first observed in the type II collagen matrix of the notochord sheath, and slightly later in the type I collagen matrix with sclerotomal origin. The nucleation and growth pattern of ...